What about the males? the C. elegans sexually dimorphic nervous system and a CRISPR-based tool to study males in a hermaphroditic species. (1st October 2020) - Walsh, Jonathon D.; Boivin, Olivier; Barr, Maureen M.
Abstract: Sexual dimorphism is a device that supports genetic diversity while providing selective pressure against speciation. This phenomenon is at the core of sexually reproducing organisms. Caenorhabditis elegans provides a unique experimental system where males exist in a primarily hermaphroditic species. Early works of John Sulston, Robert Horvitz, and John White provided a complete map of the hermaphrodite nervous system, and recently the male nervous system was added. This addition completely realized the vision of C. elegans pioneer Sydney Brenner: a model organism with an entirely mapped nervous system. With this 'connectome' of information available, great strides have been made toward understanding concepts such as how a sex-shared nervous system (in hermaphrodites and males) can give rise to sex-specific functions, how neural plasticity plays a role in developing a dimorphic nervous system, and how a shared nervous system receives and processes external cues in a sexually-dimorphic manner to generate sex-specific behaviors. In C. elegans, the intricacies of male-mating behavior have been crucial for studying the function and circuitry of the male-specific nervous system and used as a model for studying human autosomal dominant polycystic kidney disease (ADPKD). With the emergence of CRISPR, a seemingly limitless tool for generating genomic mutations with pinpoint precision, the C. elegans model system will continue to be a useful instrument for pioneering research in the fields of behavior, reproductive biology, and neurogenetics.